(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The study aimed at: • Design a test to measure the accuracy of fast play (snap attack) performance among Premier League volleyball players. • Standardize a test to measure the accuracy of fast play (snap attack) performance among Premier League volleyball players. • Establish normative levels and standardized scores for the test of fast play (snap attack) accuracy among Premier League volleyball players. The researcher employed the descriptive survey method due to its suitability for the nature of the study. The research population consisted of Premier League volleyball players, totaling (128) players, while the research sample included (94) players from (6) clubs. The researcher designed and standardized the test following established scientific procedures for test development and standardization. Data was analyzed using the Statistical Package for the Social Sciences (SPSS) to obtain the necessary results and achieve the study’s objectives.